The Influence Of Human Resources, Supervision And Career Development On The Work Achievement Of Merapi Barat Office Employees, Lahat District - Wulan Wigati; Sulbahri Madjir; Marko Ilpiyanto (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2023)
This study aims to determine the influence of human resources, supervision and career development on the work performance of employees of the West Merapi sub-district office, Lahat district. The type of research used in this research is quantitative research. The data in this study used primary data using research data collection techniques and questionnaires. The research used a survey method, the research respondents were some 35 employees. Questionnaire instruments regarding Work Performance as related variables, Human Resources, Supervision and Career Development as independent variables and analysis tools using multiple linear regression. From the results of the study it was found that 1. The Human Resources Variable partially has a significant effect on Work Performance 2. The Supervisory Variable partially has a significant effect on Work Achievement 3. Career Development Variable partially has a significant effect on Job Performance at West Merapi District Office Employees Lahat District.